An Empirical Study of the Relationship Between FDI and Ecological En-vironment Pollution-Panel Data Analysis Based on Shandong Province - Shuoyuan Zhang; Bosong Yu; Xiangmei Li; Yongyan Zhao; Mingjin Zou; Weiguo Sun (Decision Making: Applications in Management and Engineering, 2025)
As China’s economic liberalisation continues to advance, foreign direct investment (FDI) has emerged as a pivotal factor in driving economic growth. Nevertheless, with the rapid progression of industrialisation and urbanisation, the environmental implications of FDI, particularly in relation to pollution, have garnered significant attention within both academic and policy-making circles. Utilising panel data from 16 prefecture-level cities in Shandong Province spanning the period from 2016 to 2022, this study develops a hybrid model integrating Generalised Least Squares (GLS) and Gradient Boosting Regression (GBR) to investigate the influence of FDI on sulphur dioxide (SO₂) emissions and its non-linear dynamics. The findings reveal a multifaceted relationship between FDI and SO₂ emissions. In the initial stages, FDI inflows exhibit a positive correlation with SO₂ emissions, reflecting a "pollution haven" effect, whereas the anticipated pollution mitigation effects are not yet evident. After accounting for variables such as per capita income and industrial output, the impact of FDI on environmental degradation remains substantial, albeit moderated by regional policy frameworks and technological advancements. Importantly, increased fiscal expenditure amplifies the effectiveness of policy interventions in enhancing environmental quality, while technological innovation and financial investment collectively contribute to the reduction of pollutants. In conclusion, this study offers policy recommendations aimed at improving the quality of FDI inflows, bolstering governmental policy support, and facilitating the green transition of industries, with the goal of achieving a harmonious balance between economic growth and environmental sustainability.